Implementasi Kurikulum Merdeka dalam Meningkatkan Mutu Pembelajaran Anak di Sekolah Dasar Negeri 1 Catur Tunggal - Tri Desifusvitasari; Yasir Arafat; Muhammad Fahmi (Mathematics Education Study Program, 2025)
This study aims to analyze the implementation of the Independent Curriculum in improving the quality of learning at State Elementary School (SDN) 1 Catur Tunggal, Mesuji Makmur District, Ogan Komering Ilir Regency. The Independent Curriculum, which has been implemented nationally since 2022, provides flexibility for teachers in designing learning strategies that suit the needs of students. Although it provides many opportunities to improve the quality of education, its implementation faces various challenges, such as difficulties in the use of technology by teachers and adjustments to the digital platform used for curriculum administration. This study uses a qualitative approach with data collection through interviews and observations. The results of the study indicate that although there has been progress in the implementation of the Independent Curriculum, intensive training and technological support are needed so that its implementation can be optimal. With the right assistance, the Independent Curriculum is expected to be able to improve the quality of learning at SDN 1 Catur Tunggal and other schools in Indonesia.